2020
DOI: 10.1186/s12575-020-00131-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Microbiota Profiling of SARS-CoV-2 Infected Patients

Abstract: We analyzed the bacterial communities of the nasopharynx in 40 SARS-CoV-2 infected and uninfected patients. All infected patients had a mild COVID-19 disease. We did not find statistically significant differences in either bacterial richness and diversity or composition. These findings suggest a nasopharyngeal microbiota at least early resilient to SARS-CoV-2 infection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
94
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 23 publications
19
94
1
1
Order By: Relevance
“…1J ) compared with those infected with another respiratory virus (90%) or without a respiratory virus identified (86%). These findings are consistent with a study evaluating the microbiome using NP swabs in patients with mild SARS-CoV-2 infections ( 26 ).…”
Section: Resultssupporting
confidence: 92%
“…1J ) compared with those infected with another respiratory virus (90%) or without a respiratory virus identified (86%). These findings are consistent with a study evaluating the microbiome using NP swabs in patients with mild SARS-CoV-2 infections ( 26 ).…”
Section: Resultssupporting
confidence: 92%
“…We observed diverse commensal, opportunistic pathogens across the samples analyzed ( Supplementary Figure S4A available online at https://academic.oup.com/bib ). We performed a correlation of abundance of the background level bacterial pathogens with the SARS-CoV-2 quantification, but no significant correlation was found in the analyzed dataset consistent with a recent report [ 71 ]. Since we analyzed SARS-CoV-2 –positive samples from different sample sources (nasal/pharyngeal) and also of different sequencing/library types, we performed statistical tests to assess differential burden of background infectious bacteria.…”
Section: Resultssupporting
confidence: 80%
“…154 155 The association between viral load and COVID-19 severity provides some support for this hypothesis. [156][157][158] While one small study did not find significant differences in the nasopharyngeal microbiota between patients infected with SARS-CoV-2 and healthy controls, 159 other studies have reported significant differences in the oropharyngeal, lung and gastrointestinal microbiota between these groups. [160][161][162][163][164] In relation to the gastrointestinal microbiota, patients infected with SARS-CoV-2 have reduced bacterial diversity with a lower relative abundance of certain bacterial phyla including Faecalibacterium, and a higher relative abundance of others including Bacteroides.…”
Section: Microbiotamentioning
confidence: 98%